Wart - Myers, Anna. (New York : Scholastic Inc. Distributed to the trade by Holtzbrinck, 2007)
Regretting his part in his father's decision not to marry the town librarian, Stewart has many misgivings about the latest woman in their lives, although her spells and charms might make Stewart popular and improve his basketball game.
Keywords: Single-parent families -- Juvenile fiction; Remarriage -- Juvenile fiction; Paranormal fiction; Popularity -- Juvenile fiction; Schools -- Juvenile fiction; Families -- Oklahoma -- Juvenile fiction; Oklahoma -- Juvenile fiction